Retrieval of body waves with seismic interferometry of vehicle traffic: A case study from upstate New York, USA - Quiros, Diego; Brown, Larry (Seismica, 2025)
Seismic interferometry of vehicle traffic recorded by a vertical seismograph array along a highway in upstate New York has recovered surface and body waves that match the velocities of waves in the Devonian and Silurian shales. Faster arrivals extracted via interferometry align with P-waves from a controlled-source refraction survey and with local velocities derived from seismicity in the study region, while the slower linear arrivals agree with Rayleigh waves observed in the refraction survey. Traffic volume shows significant variation between peak and non-peak hours. Amplitude variation is minimal, reducing the need for normalization to extract body waves; nonetheless, better results are obtained when cross-coherence is used in conjunction with small time windows to reduce crosstalk among the vehicle sources, given their transient nature. In comparison to other seismic sources such as trains, vehicle traffic also has a broadband signature, although more compact in time as shown by spectrograms. The results presented here suggest that vehicle traffic can function as an effective seismic source for body wave interferometry under the right conditions and survey geometries.